Don't wait for someone else to fix it : eight essentials to enhance your leadership impact at work, home, and anywhere else that needs you - Lennick, Doug; Wachendorfer, Chuck; Jordan, Kathleen (Psychologist) (Wiley, 2023)
"The world needs positive leadership more than ever. Luckily, there is a large untapped source of leaders who can change the world for the better: all of us! Since each of us constantly influences those around us, by definition, everyone is a leader, not just people with formal titles. Don't Wait for Someone Else to Fix It will help everyone tap into the power of their influence to pursue a meaningful purpose, whether on the job, in the community, or at home. All it takes is "8 Essentials," a combination of moral, social, and technical imperatives core to our ability to positively influence others"--